UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU SEKOLAH DASAR NEGERI DI KECAMATAN SELAPARANG KOTA MATARAM - M Chairul Anam; Baiq Sarlita Kartiani (JUPE : Jurnal Pendidikan Mandala, 2016)
This study examines the efforts of principals in improving the professionalism of teachers Elementary School in District selaparang Mataram regency, focused on the task of the principal as a leader, innovator and motivator. This study used a qualitative approach. Data collection techniques using observation, interviews, and documentation. The informants are principals and teachers. The study found: (1) In terms of duty of the principal as leader, the study found that efforts principals include: empowerment and guidance through discussions, workshops, KKG, supervision and Self-Evaluation of Teachers (EDG), by showing the attitude exemplary, openness, discipline, and communicative among principals with all the citizens of the school. (2) In terms of duty of the principal as an innovator, the study found that the efforts made by the principal is the formulation of programs according to the situation and the demands of school, such as developing the school program healthy, clean, beautiful, and fun, as well as composing coaching program through meetings between teachers of subjects in each group. (3) In terms of the principal duties as a motivator, the study found: the efforts made by the head of the school is to maintain morale by encouraging teachers to conduct further studies, reward and punishment. Reward given to teachers who are considered to have achievements in the form of gifts and compliments. While the punishment given to teachers deemed in violation of rules and regulations in school and not able to function properly